2015
DOI: 10.1038/nmeth.3322
|View full text |Cite
|
Sign up to set email alerts
|

Catchup: a mouse model for imaging-based tracking and modulation of neutrophil granulocytes

Abstract: Neutrophil granulocyte biology is a central issue of immunological research, but the lack of animal models that allow for neutrophil-selective genetic manipulation has delayed progress. By modulating the neutrophil-specific locus Ly6G with a knock-in allele expressing Cre recombinase and the fluorescent protein tdTomato, we generated a mouse model termed Catchup that exhibits strong neutrophil specificity. Transgene activity was found only in very few eosinophils and basophils and was undetectable in bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
202
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(217 citation statements)
references
References 43 publications
5
202
0
Order By: Relevance
“…Recently, a mouse model based on Ly6g-driven Cre recombinase was developed, the Catchup mouse, which includes a fluorescent reporter allowing the function of mature neutrophils to be monitored via in vivo imaging 206 . One value of this model stems from its ability to specifically delete neutrophil-derived molecules at later stages of these cells' differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a mouse model based on Ly6g-driven Cre recombinase was developed, the Catchup mouse, which includes a fluorescent reporter allowing the function of mature neutrophils to be monitored via in vivo imaging 206 . One value of this model stems from its ability to specifically delete neutrophil-derived molecules at later stages of these cells' differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, retrograde migration of neutrophils, from the site of tissue perturbation, back to the circulation has been reported in the context of inflammation but still has to be proven in experimental animal models of cancer [127-129]. Recently, a new genetically engineered mouse model exhibited successful intravital imaging of neutrophils giving it an important advantage when, e.g., attempting to visualize neutrophil-retrograde migration [130]. …”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Importantly, we have shown that the same rapid induction of motility also occurs in neutrophils within the bone marrow of mice in vivo after systemic application of human G-CSF. However, as opposed to the in vitro situation, increased neutrophil motility in vivo is maintained over several hours, because the production of migration-activating chemokines from endothelial cells and megakaryocytes is also induced by G-CSF in the bone marrow [6,7]. Both effects together lead to the rapid release of pre-existing mature neutrophils from the bone marrow to the circulation within hours after systemic G-CSF application in mice [6].…”
Section: G-csf Rapidly Induces Neutrophil Migrationmentioning
confidence: 99%